The bioactive compound carvacrol as a potential acaricide: An assessment of its effects on the integument of female Rhipicephalus sanguineus sensu lato ticks - Lima-de-Souza, José Ribamar; de Oliveira, Patrícia Rosa; Anholeto, Luís Adriano [UNESP]; Sodelli, Luís Fernando [UNESP]; Ferreira, Allan Roberto Fernandes [UNESP]; Remedio, Rafael Neodini; Camargo-Mathias, Maria Izabel [UNESP] (Wiley, 2021)
Studies seeking control methods for infestation of Riphicephalus sanguineus sensu lato (s.l.) ticks (dog ticks) have been carried out in order to minimize damage to both the tick's hosts and the environment, the latter due to the misuse of acaricide products. In this regard, carvacrol has been used as a natural alternative against ticks as it displays several properties including acaricidal. In this context, the present study aimed to evaluate the ultramorphology and morphohistochemistry of the integument of semi-engorged R. sanguineus s.l. females exposed to different carvacrol concentrations. The findings indicate that the integument surface of females exposed to the highest carvacrol concentration (25 μl/ml) became wrinkled, suggesting dehydration or the result of integument cuticular and epithelial layer disorganization in response to the toxic product. Morphohistochemical integument layer alterations were more significant and intense in females exposed to the highest carvacrol concentration (25 μl/ml), confirming dose-dependent carvacrol action. Among other cell and tissue alterations, changes in epithelial cell shape, size, and arrangement (epidermal layer) were noted, alongside altered and pyknotic-shaped nuclei, suggesting a death process for these cells. This epithelium changed from simple cubic to stratified, also in response to the presence of the evaluated bioactive compound. Thus, the findings reported herein demonstrate that carvacrol may be an alternative for an efficient and more sustainable tick control in the near future.